The Potential Utilization of Biomass as Substitute Renewable Energy in Supporting Energy Security in Central Java - Fatonah, Rahma Dhani; Listiyani, Arvie Tri; Putri, Sindi Dwi; Insani, Rossa Dwi Nur (Journal of Clean Technology, 2025)
The utilization of rice straw as a renewable energy resource has received growing attention in the context of regional energy security and carbon emission reduction, particularly in Central Java, Indonesia. This review explores the potential of rice straw as a feedstock for bioethanol production, emphasizing its primary lignocellulosic components—α-cellulose, hemicellulose, and lignin—and key conversion stages, including pretreatment, hydrolysis, fermentation, and purification. In addition, the performance of various technologies for converting bioethanol into electricity is critically examined. Among these, Direct Ethanol Fuel Cells (DEFCs) are identified as the most efficient, offering conversion efficiencies of 40–60% and notable environmental advantages over conventional ethanol-fueled combustion generators. The findings suggest that the integration of high-efficiency conversion technologies with the region’s abundant rice straw resources could represent a strategic pathway toward a more sustainable and low-emission regional energy system.